S100A8/A9 in bleomycin-induced skin fibrosis. (22nd February 2011) - Andréasson, K; Gustafsson, R; Ivars, F; Roth, J; Vogl, T; Hesselstrand, R; Heinegärd, D; Saxne, T
Abstract : Background and objectives: Systemic sclerosis is a heterogeneous disease characterised both by inflammation and fibrosis. TLR4-dependent signalling has been proposed to play a significant role in the connection between inflammation and fibrosis in SSc. We have previously found increased levels of the TLR4-agonist S100A8/A9 in both serum and faeces of patients with SSc. In this study, we examined the role of S100A8/A9 in the pathogenesis of inflammation induced skin fibrosis in the bleomycin mouse model. Materials and methods: S100A9 -/- mice were kept on a C57 Bl/6 background. These mice lack biologically active S100A8/A9 protein complex. Wild type (WT) littermates were used as controls. In total, 40 age matched female mice were used. Skin fibrosis was induced by 12 subcutaneous injections of bleomycin over a 4 week period. Dermal skin thickness was evaluated by light microscopy and skin collagen content by measurement of hydroxyproline. Skin concentration of water and fat was evaluated after freeze-drying and fat extraction of skin biopsies with acetone respectively. Punch biopsies were taken for later mRNA quantification by rtPCR and for electron microscopy. Results: Skin thickness increased to a similar extent in WT and S100A9 -/- mice compared to saline injected animals after bleomycin treatment (262 ± 11 μm vs 263 ± 12 μm). The amount of collagen also increased to the same level in WT and S100A9 -/- mice (53 ± 1.6 vs 53 ± 0.9 μg/mm 2 ). Compared to saline injected control mice, bleomycin treatment resulted in an increase in skin water content in WT (70 ± 0.6 vs 65 ± 1.3 %; p < 0.001) but not in the S100A9 -/- mice (68 ± 1.3 vs 68 ± 0.5 %). Bleomycin treatment caused a more pronounced reduction of dry skin fat content in WT (41 ± 2.6 in saline vs 17 ± 1.6 % in bleomycin treated mice; p < 0.001) than in S100A9 -/- mice (36 ± 1.4 vs 23 ± 2.2 %; p = 0.002). Conclusion: S100A9 deficiency does not protect mice from bleomycin induced skin fibrosis. S100A9 deficiency seems to attenuate inflammatory changes of skin composition in the bleomycin mouse model of skin fibrosis.